PUERPERAL UTRRINE INVERSION: A TWO CASE REPORT - Виталий Борисович Цхай; Юлия Николаевна Глызина; Юлия Николаевна Куприянова (The Publishing House Medicine and Enlightenment, 2022)
Puerperal uterine inversion is a rare but life-threatening obstetric complication. Uterine inversion is often accompanied by postnatal hemorrhage, hypovolemic and/or neurogenic shock, which can lead to mortality. This case requires urgent obstetric and anesthetic care: immediate manual reduction of the prolapsed uterus with adequate anesthesia, prevention of bleeding and shock liquidation. This article presents clinical observations of the puerperal uterine inversion, a description of the clinical symptoms, arising complications and an analysis of obstetric tactics, treatment, diagnostic measures.